The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/min7120237
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Sequestration of Carbon Dioxide in Circulating Fluidized Bed Combustion Boiler Bottom Ash

Abstract: This paper investigates the mineral sequestration of carbon dioxide in circulating fluidized bed combustion (CFBC) boiler bottom ash. CFBC bottom ash, which originated from two sources, was prepared along with pulverized coal-fired (PC) boiler bottom ash as a control. These ashes were exposed to accelerated carbonation conditions at a relative humidity of 40% and 100%, in order to investigate the effects of humidity on the carbonation kinetics of the bottom ash. The obtained results showed that not only lime b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, based on a laboratory study, Montes-Hernandez et al [53] reported maximum CO 2 sequestration capacity of 26 kg for one tonne of fly ash. In addition, based on another laboratory study, Kim and Lee [81] observed maximum CO 2 sequestration capacity of 195 kg for one tonne of bottom ash. If the 6.8 and 1.7 million tonnes of fly and bottom ashes, respectively, being produced annually in Malaysia [73] would be used for the first 10 cm of land associated with the country's future developments (e.g., using lands associated with construction of highway [14,82]), more than 9000 ha of land could be designed for inorganic CO 2 sequestration, and 500,000 tonnes of CO 2 could be captured.…”
Section: Malaysia's Capacity For Using Soil Mineral Carbonationmentioning
confidence: 97%
“…However, based on a laboratory study, Montes-Hernandez et al [53] reported maximum CO 2 sequestration capacity of 26 kg for one tonne of fly ash. In addition, based on another laboratory study, Kim and Lee [81] observed maximum CO 2 sequestration capacity of 195 kg for one tonne of bottom ash. If the 6.8 and 1.7 million tonnes of fly and bottom ashes, respectively, being produced annually in Malaysia [73] would be used for the first 10 cm of land associated with the country's future developments (e.g., using lands associated with construction of highway [14,82]), more than 9000 ha of land could be designed for inorganic CO 2 sequestration, and 500,000 tonnes of CO 2 could be captured.…”
Section: Malaysia's Capacity For Using Soil Mineral Carbonationmentioning
confidence: 97%
“…Often used minerals include olivine ((Mg,Fe)SiO 4 ) [28], forsterite (Mg 2 SiO 4 ) [29], serpentine (Mg 3 Si 2 O 5 (OH) 4 ) [30], and wollastonite (CaSiO 3 ) [31]. Several industrial residues (such as combustion/incineration ashes, mining tailings, and metallurgical slags) also contain alkaline silicates, often more complex, such as chrysotile (Mg 3 (Si 2 O 5 )(OH) 4 ) [32] and brownmillerite (Ca 2 (Al,Fe) 2 O 5 ) [33] and, at times, amorphous (lacking crystal structure). Calcium-based minerals are usually more reactive than magnesium-based minerals, basically, because the Ca atom is larger than the Mg atom, and consequently the valence electron is less tightly bound to the Ca atom.…”
Section: Experimental Investigation Part A: Background Of Mineral Carmentioning
confidence: 99%
“…Climate change threat is promoting the development of new technologies on greenhouse gas (GHG) emissions. Given that, carbon dioxide utilization is diverse [1,2] and new technologies must be promoted to be implemented successfully. New composite materials designed to be carbonated has a great potential for CO 2 uptake, for instance, by using new additions, providing a denser final material [3].…”
Section: Introductionmentioning
confidence: 99%